Integrasi Teknologi Interaktif dalam Pembelajaran Matematika SD Berbasis Kurikulum Merdeka - Gofi Haryobel Hutasoit; Siti Mutia; Uswatun Hasannah; Riwana Simarmata (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Educational transformation through the use of interactive technology is an integral part of the implementation of the Merdeka Curriculum, especially in Mathematics learning in Elementary Schools (SD). This curriculum emphasizes a contextual, student-centered, and adaptive learning approach to the challenges of the digital era. This study aims to analyze the role of interactive technology in improving the effectiveness of Mathematics learning and developing 21st-century skills in elementary school students. Various digital media such as GeoGebra, gamification applications, and visual simulations are used to help students understand abstract concepts in a concrete and enjoyable way. The results show that technology integration supports the achievement of the Pancasila Student Profile by increasing creativity, independence, and critical thinking skills. Challenges such as limited infrastructure and teacher competency can be overcome through continuous training and development of relevant local content.